10.1007/s10697-007-0066-y (CrossRef Listing of Deleted DOIs, 2000)
Skeletal muscle insulin resistance is linked to lipid metabolism, yet whole-tissue analyses obscure how subcellular lipid remodeling contributes to metabolic dysfunction. We investigated whether Western diet induces compartment-specific changes in skeletal muscle lipid classes and fatty acid (FA) composition and how these relate to metabolic health. Western diet disrupts the relationship between lipids and metabolism. Diacylglycerol FA composition reflected dietary supply. Phospholipid remodeling was class and compartment specific. Lipid droplet-localized 1,3-diacylglycerol, phosphatidylethanolamine, and phosphatidylglycerol reflected muscle health. These results highlight subcellular lipid organization as a key determinant of muscle insulin resistance and provide a framework for identifying early lipid signatures relevant to human diabetes research.